Harmonizing Love Virtues in Music Education in Mainland China - Wai-Chung Ho (Education Sciences)
This paper explores the harmonious integration of Confucian moral values and officially sanctioned love-themed lyrics in music education across Mainland China. It addresses the main research question: What role do officially approved school songs, which embody themes of love related to three key relationships—(1) family and home, (2) teachers and friends, and (3) the Chinese Communist Party (CPC) and the Chinese nation—play in promoting the virtue of love through singing within Mainland China’s music education? By analyzing two sets of officially approved music textbooks for primary school students, consisting of a total of 24 volumes, this study reveals how love-themed lyrics serve as a medium for propagating political ideology while reinforcing traditional Confucian values among the younger generation. The research illustrates how love, as a fundamental virtue, is expressed and reinforced through these songs, highlighting their significance in fostering emotional and ethical development. The findings underscore the role of music education in cultivating a sense of community and national identity, as well as the interconnectedness of personal and collective values in shaping students’ moral frameworks.